Identification of a Rare Variant of c.1777G>A (p.G593S) in the COL1A1 Gene as the Etiology of Recurrent Osteogenesis Imperfecta by Whole-Exome Sequencing - Zhuang, Jianlong; Chen, Chunnuan; Chen, Yu'e; Luo, Qi; Wang, Yuanbai; Jiang, Yuying; Zeng, Shuhong; Xie, Yingjun; Chen, Dongmei (Frontiers in Pediatrics, 2022)
Background: Osteogenesis imperfecta (OI) is a rare heterogeneous disorder typically manifesting fragile bones and easy susceptibility to fracture. Herein, we aim to reveal the genetic etiology of recurrent OI and further investigate the genotype-phenotype correlation. Methods: Karyotype, chromosomal microarray analysis and WES were performed for genetic etiology diagnosis in the enrolled family. Western blotting analysis was carried out using the fetal skin tissue for type I collagen product expression analysis. Results: In this family, a mutation of c.1777G>A in COL1A1 was detected in the fetus who exhibit skeletal dysplasia at her first pregnancy. In this pregnancy, severe fetal skeletal dysplasia was also presented with none of chromosomal abnormality was observed in the fetus by karyotype and chromosomal microarray analysis. Further trio WES results demonstrated a de novo missense mutation c.1777G>A (p.G593S) in the fetus, which was classified as pathogenic variant according to ACMG guidelines. The recurrent mutation in two fetuses hinted gonadal mosaicism may exist in the parents, and none of mutations in COL1A1 was identified in father’s sperm DNA. Moreover, western blotting results demonstrated that no significant reduced of type I collagen product was observed in the affected fetus. Conclusions: In conclusion, we first identified a rare variant c.1777G>A in COL1A1 that leading to recurrent OI in Chinese population. Additionally, our study believe that the rare variant c.1777G>A in COL1A1 will lead to OI type II and further indicate the application value of WES in fetuses with ultrasound anomalies.